Intraprostatic locations of tumor foci of higher grade missed by diagnostic prostate biopsy among potential candidates for active surveillance - Kim, Kwangmo; Lee, Jung Keun; Choe, Gheeyoung; Hong, Sung Kyu (Scientific reports, 2016)
To establish optimal biopsy scheme for selection of candidates for active surveillance (AS) among prostate cancer (PCa) patients, information on topographical distribution of tumor foci of higher grade missed by contemporary biopsy amongst potential candidates of AS would certainly be useful. Thus we analyzed topographic distribution of tumor foci by examining prostatectomy specimens in 444 patients who underwent radical prostatectomy for low risk PCa. Anterior and posterior prostate areas were demarcated by a horizontal line drawn at midpoint of prostatic urethra. Among 444 subjects, patients with upgrading showed relatively higher prevalence of index tumor foci in anterior prostate than those without upgrading, though not reaching statistical significance (p = 0.252). Meanwhile, among 135 (30.4%) patients with very low risk PCa, patients with upgrading showed significantly higher prevalence of index tumor foci in anterior prostate than those without upgrading (52.2% vs 33.8%; p = 0.031). In conclusions, tumor foci of higher grade missed by diagnostic biopsy were mostly located in anterior prostate among very low risk PCa patients. Such finding would be concrete evidence to support the notion that more efforts are needed to increase accuracy in detecting tumor foci in anterior prostate among potential candidates for AS.